The role of intracellular and extracellular copper compartmentalization in Alzheimer’s disease pathology and its implications for diagnosis and therapy - Yu-Qi Li; Yu-Qi Li; Shuang-Shuang Tan; Shuang-Shuang Tan; Di Wu; Di Wu; Qian Zhang; Tao Wang; Gang Zheng (Frontiers in Neuroscience)
Copper is a trace element indispensable for cellular physiology, integral to cellular redox balance, and a constituent of enzyme active sites, thereby playing a pivotal role in cellular physiological function. Concerning the pathogenesis of Alzheimer’s disease (AD), the homeostatic balance of copper is perturbed both intracellularly and extracellularly. The copper–amyloid precursor protein (APP) complex facilitates the efflux of copper from cells, leading to intracellular copper depletion. Concurrently, extracellular copper associates with amyloid-beta (Aβ) plaques, precipitating copper-enriched Aβ deposition and augmenting reactive oxygen species (ROS) in the brain tissue, which finally culminates in oxidative brain damage. The interaction between copper and APP enhances the α-secretase pathway of APP processing while suppressing the β-secretase pathway, resulting in an increased production of soluble APP (sAPP), which contributes to neuroinflammation in the brain tissue. Utilizing the affinity of copper for Aβ plaques, the application of chelating agents to sequester copper within the brain can mitigate neurodegeneration associated with AD pathology. Furthermore, the use of metal imaging techniques to detect copper in the brain offers a potential diagnostic tool for the early identification of AD.